Implementation of Colored CAPTCHA - Kumar, Mandeep; Dhir, Dr. Renu (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
CAPTCHAs is an interesting of research are short forCompletely Automated Public Turing test to tell Computersand Humans Apart. The purpose of a CAPTCHA is to blockform submissions from spam bots –automated scripts thatharvest email addresses from publicly available web forms. Weintroduce a new CAPTCHA which is based on identifying thecolor of image, object or background. This actually requiresanalysis of complex contents of image, which humans usuallyperforms well but machines or robots usually do not. From alarge database of images, we select many images which havingsingle color. The main advantages of our CAPTCHA techniqueover the traditional text-based techniques are that it is languageindependent,does not require text-entry.General